Comparative Clinical, Hematological and Metabolic Profile Analysis of Five Different Laxative Protocols in Feline Constipation: A Prospective Study on Systemic Homeostasis, Acid-base Balance and Therapeutic Efficacy - Anıl Cagdas CIRAK; Bulent ELITOK (Indian Journal of Animal Research, 2026)
Background: Feline constipation is a multifactorial condition that extends beyond impaired gastrointestinal motility and is frequently associated with systemic metabolic and acid-base disturbances. Prolonged fecal retention may disrupt fluid balance, electrolyte homeostasis and acid-base equilibrium, thereby affecting multiple organ systems. For this reason, a comprehensive assessment of both clinical findings and metabolic parameters is essential for effective case management. This study aimed to evaluate the clinical, hematological and metabolic effects of five commonly used laxative protocols in cats with constipation. Methods: A total of 40 cats were included in the study, comprising 10 clinically healthy cats (control group; CG) and 30 constipated cats (study group; SG). Measurements were obtained at baseline (T0) and monitored daily throughout the treatment period (Days 1-3). Clinical findings, hematological indices, serum biochemical parameters and arterial blood gas values were assessed. Constipated cats were allocated to five treatment groups: psyllium (PHF), docusate sodium (DS), lactulose (LT), magnesium sulfate (MS) and sennoside-bisacodyl (SBC). Statistical analysis was performed using one-way ANOVA followed by Duncan’s multiple comparison test, with significance set at p less than 0.05. Result: At baseline (T0), constipated cats exhibited significant metabolic acidosis, hemoconcentration associated with dehydration and elevated inflammatory markers (p less than 0.05). All treatment protocols resulted in clinical improvement; however, lactulose and psyllium demonstrated more consistent normalization of metabolic and hematological parameters. In contrast, magnesium sulfate and sennoside-bisacodyl were associated with transient electrolyte fluctuations, particularly in potassium levels. These findings suggest that feline constipation should be considered a systemic disorder with notable metabolic consequences and that lactulose and psyllium provide more stable therapeutic outcomes.